Digital Fatigue and Consumer Resilience: A Conceptual Framework for Global Omnichannel Marketing - Stefani Angmalisang; Vidy Mewengkang; Delfia Manampiring; Ditha Lengkong; Mikaela Gonta; Claudi Paendong; Arini Langingi; Novita Ronsul; Jesica Tundundatu; Stevia Wahir (Penerbit Jurnal Indonesia, 2026)
The rapid growth of digital technology and global connectivity has transformed consumer interactions, yet it has also led to increasing levels of digital fatigue emotional and cognitive exhaustion resulting from excessive digital engagement. This phenomenon challenges consumers’ ability to sustain attention, trust, and satisfaction in an omnichannel marketing environment, where seamless integration across online and offline platforms is crucial. This conceptual paper aims to develop a theoretical framework that explains the relationship between digital fatigue and consumer resilience in the context of global omnichannel marketing. Using a literature-based analytical approach, this study synthesizes findings from recent research on digital behavior, psychological resilience, and global marketing adaptation between 2020 and 2025. The analysis highlights that while digital fatigue weakens consumer engagement and loyalty, resilience functions as a psychological buffer that enables adaptation and sustained participation in omnichannel interactions. Moreover, cultural and contextual factors moderate the extent to which consumers cope with digital stress in different markets. The proposed conceptual framework contributes to international marketing theory by emphasizing the interplay between technological pressure, consumer psychology, and cultural adaptation. Practically, it provides insights for global marketers to design strategies that minimize digital fatigue while fostering resilient and sustainable consumer relationships across diverse cultural settings.